An integrated patient journey mapping tool for embedding quality in healthcare service reform. (10th June 2016) - McCarthy, Stephen; O'Raghallaigh, Paidi; Woodworth, Simon; Lim, Yoke Lin; Kenny, Louise C.; Adam, Frédéric
Abstract: The healthcare sector is a highly regulated environment that is subject to numerous constraints. Standards around medical protocol, medical device certification, and data protection ensure that the wellbeing and privacy of patients is protected during all encounters with the healthcare system. However, a gap has opened up between the need to meet these constraints, improve performance, and also deliver good patient experience. For example, the medical protocol for hypertension during pregnancy establishes a set of clinically validated treatment guidelines, but does not consider the unique nature of patient experience. We assert that design research principles can be used to create visual tools that pay homage to these constraints and performance improvement goals without compromising patient experience. In this paper, we describe such a tool that has been developed during a healthcare project using a human-centred design research approach. The integrated tool for patient journey mapping addresses the shortcomings of existing methodologies by supporting multidisciplinary practitioners in designing healthcare solutions that meet the demands of existing constraints, performance improvement, and patient experience. In addition, we document how patient journey maps were used on the project to facilitate collaboration among a team of multidisciplinary stakeholders.